Influence of surface heterogeneities on the formation of diffusion-limited aggregates - Nazzarro, Marcelo Sandro (2002)
In the present paper, we study the influence of surface energetic heterogeneities on the main features of fractal aggregates generated through a diffusional mechanism. The diffusion-limited aggregation (DLA) model was introduced by Witten and Sander (Phys. Rev. Lett. 47 (1981) 1400) and has stimulated growing interest in the study of a variety of nucleation and growth processes since then. In the DLA model, growth begins with a seed particle in the center of a two-dimensional lattice. Then, individual particles are launched uniformly from a launching circle, sufficiently big, and they perform activated random walk until they stick to the growing cluster. The DLA clusters formed in this way are fractal objects with a well determined fractal dimension df=1.72±0.02. In order to include surface heterogeneities, we have used a square lattice with two kinds of sites which are assembled in such a way that the resulting structures have patchwise topography. Lattices formed by collections of orderly localized patches of different sizes are generated. DLA clusters are clearly affected in their morphology due to the presence of the surface heterogeneities which is analyzed and explained in terms of the different energetic topographies.